Pelayanan Pastoral Berbasis Ekologi Sebagai Upaya Pelestarian Lingkungan Hidup - Budiman, Sabda; D. A. Laukapitang, Yunus (Institut Agama Kristen Negeri Toraja, 2024)
There are several problems encountered in pastoral ministry, namely focusing too much on human services. In addition, sometimes the implementation of pastoral ministry also has a negative impact on the environment such as excessive use of plastic, paper, and energy so that it seems that the church is not environmentally friendly and can become a stumbling block for society. The purpose of this article is to highlight and explain various forms of ecology-based pastoral care as a form of church involvement in environmental conservation. The author uses a qualitative research method with a literature study approach. The discussion in this study emphasizes various forms of ecology-based pastoral services such as liturgy, fellowship, teaching, and evangelism. In addition, there are several efforts proposed by the author as a form of organizational church involvement in preserving the environment such as forming an environmental care community, forming a waste bank, and using renewable energy as an alternative energy. This research shows that ecology-based pastoral care has great potential to be an effective instrument in building church communities that care for the environment and contribute positively to environmental conservation.